Financial Crises, Social Impact, and Risk Management : Lessons and Challenges - Guerschanik Calvo, Sara (World Bank, Washington, DC, 2013)
This paper reviews lessons learned from financial crises; describes the channels of transmissions of economic booms and busts in crisis vulnerable economies; and highlights the central role of external factors, credit and the mitigating role of the public sector, with a broad focus on the impact on the poor from developing countries. Financial crises increase poverty, may increase income inequality and may deteriorate human development indicators such as health and education. Public sector credit and international reserves have proven effective in preventing a fully-fledged financial crisis, as has concurrent external support, though these mitigating actions have not been effective in preventing a drop in gross domestic product (GDP) even in economies perceived to be well managed such as Chile in 1999-2000 and 2009. While public banks provide an additional tool for crisis management in the short run, credit misallocation and efficiency losses due to politically motivated lending are still widespread.